Government Regulations on Innovations (Journal of Economic Research & Business Administration, 2016)
The given article is devoted to the problems of the governmental regulations of innovative actions. As shows the experience of developed countries the innovative development of country without an interference of the government don’t lead to the expected results, that is why the con-duction and implementation of innovative and investigative policy should remain as the governmental task. The aim of the governmental regulations of innovative activity should become the properly conducted innovative policy. Innovative policy of the state by itself presents the set of forms, methods and directions which influence on the production of new prod-ucts and technologies.
Keywords: Innovations; innovative actions; innovative policy; new products and technologies; scientific and technological progress.